2007
DOI: 10.1063/1.2803067
|View full text |Cite
|
Sign up to set email alerts
|

Nonalloyed Cr∕Au-based Ohmic contacts to n-GaN

Abstract: Nonalloyed Cr/ Au-based metal contacts to n-GaN have been demonstrated. The deposited Au/ Cr/ n-GaN contacts exhibited a specific contact resistance ͑ c ͒ of approximately 5.6 ϫ 10 −5 ⍀ cm 2. Although the nonalloyed Ti/ Al-based contacts to n-GaN can also exhibit a comparable c value, their thermal stability is inferior to the Cr/ Au-based contacts. This could be attributed to the fact that Al tends to ball up during thermal annealing. Thus, the surface morphology of most of the annealed Ti/ Al-based contacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 10 publications
2
49
0
1
Order By: Relevance
“…• C появля-ется неомичность контакта металл−полупроводник, характеризующая-ся нелинейной вольт-амперной характеристикой [4,5]. Поскольку СВЧ МИС в процессе изготовления проходят технологические операции с температурой процесса 300−350…”
Section: поступило в редакцию 14 июня 2017 гunclassified
“…• C появля-ется неомичность контакта металл−полупроводник, характеризующая-ся нелинейной вольт-амперной характеристикой [4,5]. Поскольку СВЧ МИС в процессе изготовления проходят технологические операции с температурой процесса 300−350…”
Section: поступило в редакцию 14 июня 2017 гunclassified
“…The Ti/Al-based contacts are the most popular metal schemes for n-GaN due to their low work function. However, they do not alleviate the need for high annealing temperatures to form intermetallic alloys further with low work function at the metal/semiconductor interface [5]. The effect of thermal annealing on the electrical property of metal contacts was different between the Ti/Al-and Cr/Au-based contacts on the Ga-face n-GaN surface [5].…”
Section: Introductionmentioning
confidence: 98%
“…However, they do not alleviate the need for high annealing temperatures to form intermetallic alloys further with low work function at the metal/semiconductor interface [5]. The effect of thermal annealing on the electrical property of metal contacts was different between the Ti/Al-and Cr/Au-based contacts on the Ga-face n-GaN surface [5]. Several reports have recently revealed that Al-based metal contacts could form low-resistivity Ohmic contacts on the N-face n-GaN surface [6,7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Two of the most used adhesion layers are chromium [44,45] and titanium. Although they allow for a smoother and thinner waveguide, neither of these metals has the optical characteristics superior to gold; thus, the plasmon behavior can worsen significantly.…”
Section: Gold Thin Filmsmentioning
confidence: 99%